"Hiding In Plain Sight": Seeing and Forgetting Reality in David Foster Wallace's Oblivion - Sircy, Jonathan (Christianity & literature, 2022)
Critics routinely note the bleak world portrayed in David Foster Wallace's Oblivion: Stories. This article argues that the collection's pessimism comes from its characters' inability to see what is "hidden in plain sight" about the world's most "real and essential" features. These phrases come from Wallace's famous Kenyon Commencement Address, This Is Water. I argue that Oblivion is a fictional companion to that speech, stories of what happens when the most important features of reality go unseen. In contrast with Wallace's other work, where elements of Christianity are openly accepted or rejected, Oblivion's characters remain blind to God.